The Impact of Digital Social Networks on the Social Values of Saudi Youth (The International Journal of Educational Sciences and Arts, 2024)
Social media networks have emerged among young people in a way that has made digital platforms dominating on virtual reality for many users, which has made them win the bet on media competition between media institutions and communicating platforms to attract more users. In the midst of this demand for digital social platforms, questions arise regarding the nature of the changes and effects that these platforms reflect on users. Despite the fact that this path has been previously addressed by a number of researchers, questions related to these effects still exist due to the change in communication content and the increase in consumption by users, which suggests a change in perceptions, whether negatively or positively. Therefore, many research questions arise here related to intellectual influences in terms of the type of influence that digital social platforms reflect on university student users and to what extent this influence reaches and what are the individual differences due to demographic characteristics.Given that the social aspect is the final result of common customs and traditions, which stem from religious culture, socialization, education and upbringing, this study addresses the intellectual and social effects of digital social media platforms on university students (King Abdulaziz University) due to the great diversity that the university contains in terms of social and cultural backgrounds, which reflects a clearer and more accurate picture than some other universities located in areas with less cultural and social diversity. The study included a diverse sample of university students, numbering around 264 male and female students. The study showed that intellectual effects tend to be largely negative, as variables related to the positive effects of social media networks on social values ​​received a weak approval rate among the study sample, for example: what is published of news and events on social media networks about social values ​​is positive (45.20%), social media networks help in preserving social values ​​(44%), social media networks enhance the building of social values ​​(47.20%), with the emergence of demographic differences due to gender between male and female students in some other variables regardless of academic specializations. The study includes at the end a number of outputs and recommendations that can contribute to reducing the negative effects among university students, which increases the chances of influencing more than being influenced.
Keywords: Dialogue Methods; Social Values; Communication Influence; Social Networking Sites; Twitter; Dialogue Issues; Social Discussions